A Bibliometric Study of Postgraduate Theses in Library and Information Science with Special Reference to University of Kelaniya and University of Colombo, Sri Lanka - Angammana, A.M.S.; Jayatissa, L.A. (My University, 2016)
Bibliometric analysis is used by an increasing number of researchers in the field of Library and Information Sciences (LIS). University libraries, which spend large amounts of fund annually to acquire information sources, face enormous problems related to the selection and the weeding out of publications. To minimize or overcome these problems, bibliometric studies are often used by librarians. The objective of the study is to ascertain bibliometric features visible in the field of Library and Information Sciences. For this purpose, 50 theses submitted for the Master of LIS degree (MLS) of the University of Colombo and 20 theses submitted for the Master of Social Science in LIS (MSSc) of the University of Kelaniya were analyzed. From those 70 theses, a total of 4,901 citations were extracted using the lists of references and bibliographies provided as the main source of primary data. These citations were cross classified and tabulated according to a number of variables. It was revealed that books were the most heavily used source material, accounting for 39% of citations, while journals category coming next with 34% of citations. Most heavily used book was the “Organizational Behavior” by Robbins, (2001). “College and Research Libraries” is found to be the most heavily used journal. Within the span of 11 year study period, 485 journals were cited. A total of 1, 664 citations originated from these journals. The journal “College and Research Libraries” ranks as the first in the core journals list with 66 citations. “Library news” which ranks the second place accounts for 52 citations. The mean half-life of all citations is almost 9 years, while the mean half-life for journals and books are 7 years and 13 years, respectively. Findings of the study are in conformity with the previously reported research findings, which also reports that books as the main source material for research studies in LIS fields.
Senior Assistant Librarian, University of Sri Jayewardenepura. Email:santha@sjp.ac.lk, Librarian, University of Kelaniya, Kelaniya. Email:jaya@kln.ac.lk
Keywords: Academic Libraries; Bibliometrics; Citations; Library and Information Sciences